Histone deacetylases in viral infections - Herbein, Georges (Springer-Verlag, 2010)
Chromatin remodeling and gene expression are regulated by histone deacetylases (HDACs) that condense the chromatin structure by deacetylating histones. HDACs comprise a group of enzymes that are responsible for the regulation of both cellular and viral genes at the transcriptional level. In mammals, a total of 18 HDACs have been identified and grouped into four classes, i.e., class I (HDACs 1, 2, 3, 8), class II (HDACs 4, 5, 6, 7, 9, 10), class III (Sirt1–Sirt7), and class IV (HDAC11). We review here the role of HDACs on viral replication and how HDAC inhibitors could potentially be used as new therapeutic tools in several viral infections.